PRESERVATION OF INDIGENOUS KNOWLEDGE AND CULTURAL HERITAGE AMONG THE VATSONGA THROUGH EDUCATION - Chauke, Tinyiko Esther (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study explores the preservation of Vatsonga Indigenous Knowledge Systems (VIKS) and cultural heritage as a foundation for sustaining community identity, intergenerational wisdom, and cultural diversity. It emphasizes the importance of culturally grounded education amid globalization and the Westernization of schooling, which erode Vatsonga traditions. Guided by Decolonial Education Theory and epistemological justice, the study conceptualizes integrating Indigenous epistemologies into formal education as both an intellectual necessity and a social imperative. Using a qualitative design, data were collected from 18 participants—Vatsonga elders, educators, policymakers, and secondary school learners—through interviews, focus groups, and curriculum content analysis. Findings reveal that embedding IKS enhances cultural pride, identity, belonging, and educational equity while promoting cultural sustainability. System-level recommendations include developing culturally responsive materials, formalizing collaboration with elders as knowledge holders, and strengthening policy frameworks supporting Indigenous knowledge integration. The study concludes that systemic incorporation of Vatsonga Indigenous knowledge into South African education is vital for cultural preservation, decolonization of learning spaces, and intergenerational knowledge transmission. It contributes to decolonial education scholarship by demonstrating how localized Indigenous epistemologies can be operationalized within curricula as a transformative strategy for advancing epistemic justice and cultural renewal. The research calls for national policy adoption of IKS integration to affirm the cultural rights and intellectual sovereignty of Vatsonga learners and communities.